Career Adapt-Abilities Scale-Short Form: Validation for Use in India - Suchitra Pal; Lalatendu Kesari Jena
The Career Adapt-Abilities Scale (CAAS) is popular among researchers and validated in many countries but has not yet been tested for the Indian context. This study examined the CAAS Short Form (CAAS-SF) among a sample of Indian business school students. The CAAS-SF consists of four subscales, each with three items measuring concern, control, curiosity and confidence as psychosocial resources. A sample of 369 Indian business-school students with human resource management as major participated in the scale validation process. The internal consistency estimates for the subscales and total scores were found to be comparable or better than previous CAAS-SF assessments. Based on this study$1 (Bs findings, the CAAS-SF appears to be appropriate for measuring career adaptability resources in Indian business school students.s